Gender-oriented vocabulary in advertising texts - Malomoshnova, A.V.; Musinova , G.S. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2023)
Lexical means of expressing gender orientation in advertising texts are considered in the article. The relevance of the chosen topic is due to the need to take into account gender specificity in advertising slogans, which contributes to the accurate pragmatic impact and more effective construction of advertising communication. The study was based on the texts presented in the ads of popular magazines "Maxim" and "Cosmopolitan". The article considers examples of advertising texts with the indication of the lexical means of gender orientation, which supports the conclusion that the lexical means of gender orientation in the advertising text can include the vocabulary indicating the gender of the addressee, which contributes to the orientation of the advertising campaign to a specific target audience. The article presents an analysis in quantitative and percentage terms, which clearly demonstrates that, for example, adverbs in advertising for a female audience are much more common than in male advertising. The use of verbs in advertising texts, both for male and female advertising, is a priority, since the main semantic load is expressed through them. However, verbs predominate in male-oriented advertising texts, which indicates a man’s ability to take decisive action. The verb is expressive and meaningful, dynamic.